Nīḷakaṇṭha smārakī - Miśra, Sadāśiba, 1909-; Dāśa, Nīḷakaṇṭha, 1884-1967 (Paṇḍita Nīḷakaṇṭha Smrti Samiti : distributor, Mayur Publications, 1982)
Commemoration volume on Nilkantha Das, 1884-1967, Oriya poet, educationalist, and national leader; comprises articles, and reminiscences, with a selection from his works.